2011
DOI: 10.1124/jpet.111.180984
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Characterization of Aristolochic Acid Transport by the Kidney

Abstract: Consumption of herbal medicines derived fromAristolochia plants is associated with a progressive tubulointerstitial disease known as aristolochic acid (AA) nephropathy. The nephrotoxin produced naturally by these plants is AA-I, a nitrophenanthrene carboxylic acid that selectively targets the proximal tubule. This nephron segment is prone to toxic injury because of its role in secretory elimination of drugs and other xenobiotics. Here, we characterize the handling of AA-I by membrane transporters involved in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…It was recently shown that organic ion transporters (OATs) 1 and 3 mediate concentrative uptake of AA-I ( 1 ) in the mouse proximal tubule and may be involved in the site-selective toxicity of this nephrotoxin. 31 Thus, in the IPK, OATs 1/3 likely mediate basolateral uptake of AA-I ( 1 ) from the perfusate. The nephrotoxin then undergoes demethylation or nitroreduction in the proximal tubule, followed by secretory efflux of metabolites to the urine and/or reabsortive efflux of metabolites to the perfusate.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that organic ion transporters (OATs) 1 and 3 mediate concentrative uptake of AA-I ( 1 ) in the mouse proximal tubule and may be involved in the site-selective toxicity of this nephrotoxin. 31 Thus, in the IPK, OATs 1/3 likely mediate basolateral uptake of AA-I ( 1 ) from the perfusate. The nephrotoxin then undergoes demethylation or nitroreduction in the proximal tubule, followed by secretory efflux of metabolites to the urine and/or reabsortive efflux of metabolites to the perfusate.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 In vitro studies confirmed that AAI is much more cytotoxic compared with AAII because of the presence of a methoxy group in position 8. 31,32 On the other hand, the carboxyl group rather than the nitro group is important to facilitate AA entry into tubular cells via OATs. Finally, nitroreduction results in N-hydroxy-aristolactam formation, and these metabolites bind covalently to the exocyclic amino groups of adenine or guanine forming AAspecific DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…51 The elevated levels of dA-AL-I adducts in renal cortex likely are due to the active transport of AA-I into the cortex by organic ion transporters, which also may be involved in the site-selective toxicity and renal elimination of AA-I. 69 Of the 148 Taiwanese subjects assayed by MS, 132 subjects harbored dA-AL-I at a level above 0.3 adducts per 10 8 DNA bases (the LOQ value) in the renal cortex (unpublished data). 25,45,51 The mean level of dA-AL-I was 16.0 adducts per 10 8 DNA bases with a 95% confidence interval range from 10.1 to 21.0 adducts per 10 8 DNA bases (a value of 0.15 adducts per 10 8 DNA bases, one-half the LOQ value for non-positive samples, was used for the calculation of the 95% CI).…”
Section: Uplc-esi/ms3 Measurement Of Da-al-imentioning
confidence: 99%